Donedavno pojmovanje glasbenega modernizma - "adornovska zmota"? - Salmič Kovačič, Karmen (Muzikološki zbornik, 2017)
The paper explores one of the key findings of the until recently prevailing view on music history and modernism in the music of the 20th century as being a national and ideological construct, conceived by the supporters of the self-proclaimed mainstream of the Second Viennese School. In current musicological literature, the aforementioned construct is frequently being criticized. We designated this an "Adornian mistake". Slovenian musicologists have also fallen victim to this misunderstanding, which simply confirms the widespread intercultural prevalence of the phenomenon.
Keywords: 20.st.; adornovska zmota; glasba; glasbeni modernizem; klasicistični modernizem; neoklasicizem